Correlation between clinical measurement scales on gross motor function in children with spastic cerebral palsy - Shimaa Reffat; Alaa Fahmy AL-Nemr (SpringerOpen, 2024)
Abstract Background Children with cerebral palsy (CP) may have different gross motor impairments which in sequence affecting their life occupations. The purpose of the study is to investigate the correlation between Gross Motor Function Measurement-66 (GMFM-66), the test of Bruininks-Oseretsky Motor Proficiency (BOTMP), and the Peabody Developmental Motor Scale-Second Edition (PDMS-2) in young children with CP. Methods A correlational study was applied on 50 children aged from 4 to 6 years (30 girls, 20 boys) with spastic CP. Results The Pearson correlation coefficient between the GMFM scale and PDMS-2 motor quotients, and its subscales (stationary, locomotion, and object control) and also between GMFM and BOTMP gross motor quotients and its subscales (strength, agility, and body coordination) were statistically significant. Spearman's coefficients between the grade of the Gross Motor Classification System (GMFCS) and the PDMS-2 Gross Motor Composite, BOTS-2, and its subscale results were also statistically significant. Conclusion The three measurement scales, GMFM- 66, BOTS-2, and PDMS-2, are significantly related. Therefore, GMFCS is useful in predicting movement performance in children with CP and correlated with predictive guidance in treatment development. Trial registration ClinicalTrials.gov Identifier: NCT06124352.